If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-147=7x+3(-6x-5)
We move all terms to the left:
-147-(7x+3(-6x-5))=0
We calculate terms in parentheses: -(7x+3(-6x-5)), so:We get rid of parentheses
7x+3(-6x-5)
We multiply parentheses
7x-18x-15
We add all the numbers together, and all the variables
-11x-15
Back to the equation:
-(-11x-15)
11x+15-147=0
We add all the numbers together, and all the variables
11x-132=0
We move all terms containing x to the left, all other terms to the right
11x=132
x=132/11
x=12
| 24=4+10x | | 1/2(8x+10)=1/3(15x+15) | | 2|x+2|+8=10 | | 6x+3=(3x+5) | | G(x)=x4-4x | | 2n^2-20n+20=0 | | 2.4x-14=19 | | 5m+10=5m+9 | | -9(t+-2)=4(t-15) | | 6x+3(4+x)=18 | | 3y+9=2y-9= | | 2x=360÷4 | | F(x)=x3-3x | | 3x5.2=2-5x | | (x+3)^2=9 | | 10x^2+6x+20=0 | | 3(5z-(3))-(4(2z+1))=5z-(2) | | 2(2y-4)+12=-y+8+5y | | F(x)=x5+5x | | (5.15-2x)x(7.65-x)=0 | | 1/2(3x+4)=3+2 | | 6x-3(x-5)=-(2x+15) | | -4(2n-5=-28 | | 5(3-d)=2+1 | | 9/8=3w/24 | | 12x^2-10x-28=0 | | 28+8x=8(x+3) | | x^(2/3)+9x^(1/3)+8=0 | | -9/8=3w/24 | | 23=3n-7 | | 2x2−40x+200=0 | | F(x)=x3+5x |